The Impact of Harvester Income Levels on the Welfare of Harvester Families on Oil Palm Plantations - Andi Lelanovita Sardianti; Siti Nora Novel; Puspita; Humairo Aziza; pandhu rochman suosa putra; Muhamad Yazid Bustomi (Jurnal Loupe, 2025)
Palm oil plantations are a strategic sector that plays a significant role in absorbing labor, particularly harvesters. Harvesters' income levels are a major factor influencing their families' well-being. This study aims to determine the income received by harvesters and analyze the level of family welfare of harvesters on oil palm plantations at PT. London Sumatra Indonesia Tbk, located in Tanjung Makmur Estate, East Kalimantan. The research method used was descriptive quantitative, with purposive sampling of six harvesters who met the research criteria. Data were obtained through interviews, observation, and documentation, then analyzed by comparing harvester income to the Regency/City Minimum Wage (UMK). The results showed that the average harvester income was Rp 4,674,565 per month, with a net income of Rp 3,673,124 per month after deducting Rp 732,860 per month for routine household costs and expenses covered by the company. Based on the Regency/City Minimum Wage (UMK) standard of Rp 3,711,017.82, the harvester income level was above the UMK and thus met the wage eligibility standard. This indicates that the harvester's income was able to meet basic family needs, leave some income for savings, and contribute positively to the welfare of the families of harvesters on oil palm plantations.